NILAI KETUHANAN, AKHLAK, DAN KEMANUSIAAN DALAM EKONOMI ISLAM: PERSPEKTIF AL-QURAN - Hermansyah (STAI DI AL-HIKMAH, 2023)
This paper analyzes the divine, moral and economic values contained in the Al-Qur'an. This research uses an extensive literature study approach from journals, books, Qur'an commentary, and online references that are in accordance with the theme of this research. The research findings state that Islamic economics has its own uniqueness and privileges compared to all economic systems that exist in the world today such as the capitalist economy and the socialist economic system. Among these special values include divine and human values as well as morals. With these three values, Islamic economics overcomes all the problems that exist in society and provides solutions for the welfare of human life and their prosperity in this world and in the hereafter. While the capitalist economy teaches its adherents to get as much profit as possible regardless of how to achieve it and also does not pay attention to human and moral values so that socio-economic inequality occurs in society as a result of practicing capitalist economic theory